2005
DOI: 10.1101/gr.3728305
|View full text |Cite
|
Sign up to set email alerts
|

The mouse genome

Abstract: The house mouse has been used as a privileged model organism since the early days of genetics, and the numerous experiments made with this small mammal have regularly contributed to enrich our knowledge of mammalian biology and pathology, ranging from embryonic development to metabolic disease, histocompatibility, immunology, behavior, and cancer. Over the past two decades, a number of large-scale integrated and concerted projects have been undertaken that will probably open a new era in the genetics of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 84 publications
0
57
0
2
Order By: Relevance
“…21,22 This level of variation will be similar between other pairs of common inbred strains, such as 129, DBA, BALB/c, or AKR. 23 To illustrate the problem, we list in Table 2 the genes whose expression levels show common variations resulting from the passenger region flanking the Pon3 gene knockout shown in Figure 2. Altogether, about 40 genes exhibited variations in transcript levels, and a number of these have been found to affect atherosclerosis in transgenic studies, including paraoxonase, 2 lipoprotein lipase, and Cxcr6.…”
mentioning
confidence: 99%
“…21,22 This level of variation will be similar between other pairs of common inbred strains, such as 129, DBA, BALB/c, or AKR. 23 To illustrate the problem, we list in Table 2 the genes whose expression levels show common variations resulting from the passenger region flanking the Pon3 gene knockout shown in Figure 2. Altogether, about 40 genes exhibited variations in transcript levels, and a number of these have been found to affect atherosclerosis in transgenic studies, including paraoxonase, 2 lipoprotein lipase, and Cxcr6.…”
mentioning
confidence: 99%
“…A particular advantage of using cells from humans compared with mice is the frequent and substantial species differences in their immune systems; for example, the absence of an exact homolog of human IL-8 in mice (41,42). Using small hairpin RNA (shRNA) knockdown technology, we generated stable human monocytic cell lines with massively reduced expression of caspase-4, and demonstrated that caspase-4 plays an important role in the classical LPS-induced TLR4-signaling pathway that leads to NF-B activation and consequent up-regulation and secretion of IL-8 and CCL4.…”
mentioning
confidence: 99%
“…12 Nonetheless, significant differences between mice and humans exist in the development of the immune system as well as in the activation of both the innate and adaptive immune responses. Concerning macrophage polarization, both similarities and differences have been reported between man and mouse, as summarized in the Table. In particular, one of the best surface markers used for determining the distribution and function of mouse macrophages is Ly-71 (F4/80), 13,30 which is believed to play an immunoregulatory role through the interaction with an unidentified cellular ligand expressed by other immune effectors cells.…”
Section: Of Mice and Men…in Macrophage Polarizationmentioning
confidence: 99%